Rancang Bangun Sistem Informasi Rekam Medis Berbasis Web - Suprayoga Prabowo, Daniel Wahyu; Triono, Joko (LPPM Universitas Merdeka Madiun, 2021)
Abstractâ€” A medical officer in conducting health services must make a medical record and must report the medical records to the government hospital or local health department. With these problems in place, this study seeks to build a web-based medical registration system. The system built is expected to be able to accelerate the writing of medical records and provide information to the public wherever and whenever that can be accessed via the internet. Furthermore, in terms of reporting between medical officers and health services faster because medical staff can report the patient's medical record recapitulation through a web-based system, and the health department can print reports on medical records through the system, in addition medical staff can interact with the public by making announcements , health information counseling, and comments relating to medical services.Â Keywordsâ€”: medical records ; information systems; web.